The Role of Leadership in Success of 5R Culture: A Systematic Literature Review - Fani Akmaliyah Safitri; Achmad Husen; Dian Alfia Purwandari; Nida’ Farah Abiyya; Hasnah Lidiawati (Jurnal Syntax Admiration, 2025)
The 5R (Concise, Neat, Clean, Careful, Diligent) work culture is the foundation of modern work environment management that aims to create an efficient, clean, safe, and productive workplace. However, the implementation of this principle is highly dependent on the active role of the organization's leader. This study aims to examine the role of leadership in the success of the 5R culture through a systematic literature review of 16 academic articles from various sectors: manufacturing industry, MSMEs, health services, education, and SOEs. The method used is a thematical-narrative approach with classification based on sector, leadership style, implementation strategy, and successful implementation of the 5R. The results of the study show that the success of the 5Rs is strongly influenced by four key leadership roles: facilitator, role model, communicator, and evaluator. In the large industrial sector, the MSME sector, the education and healthcare environment, design implementation, local leadership play a role in the synchronization of work values and practices. The discussion emphasized the importance of contextual and transformational leadership to ensure the sustainability of the 5R culture. Many studies indicate that the 5R culture often fails to survive due to weak evaluation and inconsistency of leaders. A value-based leadership training approach and visual work design are also recommended to strengthen the internalization of the 5R principles. This article concludes that leadership has a crucial influence on the success of the 5Rs in various organizational contexts. The leadership role framework built in this study can be used as a guideline for training, organizational development, and evaluation of work culture policies. Further research based on primary data is needed to test the effectiveness of leadership interventions on the success of cross-sector work culture.